Título Padrão - Barboza da Silva, Dagualberto; dos Santos Leonardo, Camila; Pereira Barros, João Paulo; Atem Gonçalves de Araújo Costa, Érica; Sales Macedo, João Paulo; Azigon, Talles; Silva, Leonardo (Revista de Psicologia, 2023)
This article aims to discuss the reinvention of territories of peripheral childhoods and youths based on photographs and poems produced by photographer (to be identified if the article is accepted, as it acts as a participant in the writing of the article) and poet (to be identified if the article is accepted, as it acts as a participant in the writing of the article) as a way of re-existing in Fortaleza. These are problematizations arising from the realization of an inter(in)vention research of cartographic ethos, with these young people, in which images and poems emerge as playful devices in the production of counter-hegemonic movements against the “official images” historically imposed on the peripheries. Through these photographs and poems, and, therefore, through art, the claim of territories portrays and narrates childhoods and youths on the outskirts of Fortaleza from their strengths and not from their precariousness. As an experiment, the article was produced from these poems and photographs, in addition to counting on the participation of (to be identified if the article is accepted, as it acts as a participant in the writing of the article) and (to be identified if the article is accepted, as it acts as a participant in the writing of the article) in the elaboration of the text as a decolonial movement (dis)inhabiting academic writing.